Healing the Mind and Soul with Art and Music - Jennifer Fortuna (Scholarworks @ WMU, 2020)
Gracie Fisher, an artist and composer based in Santa Barbara, California, provided the cover art for the Fall 2020 edition of The Open Journal of Occupational Therapy (OJOT). "The Fruit of Spirit" is a 16" x 20" oil painting on canvas. When a rare neurologic condition left Gracie paralyzed from the neck down, art and music helped to heal her mind and soul. Upon returning home from the hospital, Gracie's wish was to create an inclusive environment where children of all abilities could engage in art and music. She founded the Grace Fisher Foundation so others could experience the healing nature of occupation. Gracie believes art comes in many forms. With the right environment, tools and supports, anyone can create.